Reproductive autonomy and the experience of later-than-desired pregnancy: results from a cross-sectional survey of reproductive-aged women in Uganda - Suzanne O. Bell; Fredrick Makumbi; Isabella Sarria; Simon P. S. Kibira; Linnea A. Zimmerman (BMC, 2024)
Abstract Background The focus of reproductive autonomy research has historically been on the experience of unintended pregnancy and use of contraceptive methods. However, this has led to the neglect of a different group of women who suffer from constraints on their reproductive autonomy-women who experience pregnancies later than they desire or who are unable to become pregnant. This study examines the extent of later-than-desired pregnancy among women and evaluates the sociodemographic and reproductive factors associated with this experience in Uganda. Methods We use data from the Performance Monitoring for Action Uganda 2022 female survey. We restricted the nationally representative sample of reproductive-aged women to those who were currently pregnant or who had ever given birth (n = 3311). We compared the characteristics of women across fertility intention categories (wanted pregnancy earlier, then, later, or not at all) of their current or most recent birth and used multivariable logistic regression to examine factors independently associated with having a pregnancy later than desired compared to at a desired time. Results Overall, 28.3% of women had a later-than-desired pregnancy. Nearly all sociodemographic and reproductive characteristics were associated with the desired pregnancy timing of women's current or most recent pregnancy. Having higher education [adjusted odds ratio (aOR) 2.41, 95% confidence interval (CI) 1.13-5.13], having sought care for difficulties getting pregnant (aOR 2.12, 95% CI 1.30-3.46), and having less than very good self-rated health (good health aOR 1.74, 95% CI 1.12-2.71; moderate health aOR 1.77, 95% CI 1.09-2.86; very bad health aOR 4.32, 95% CI 1.15-16.26) were all independently significantly associated with increased odds of having a later-than-desired pregnancy. Being nulliparous (aOR 1.98, 95% CI 0.99-3.95) was also borderline significantly associated with having a later-than-desired pregnancy. Conclusions Identifying those who have later-than-desired pregnancies is essential if we seek to make progress towards supporting women and couples in achieving their reproductive goals, not just preventing pregnancies. Research on desired pregnancy timing in sub-Saharan Africa should be expanded to capture later-than-desired pregnancies, a population which is invisible in existing data. This work has public health implications due to commonalities in the factors associated with mistimed and unintended pregnancies and their link to poorer health and potentially poorer pregnancy outcomes.